Lead isotope and age studies of uranium and lead minerals from the British Isles and France - Pockley, R (1961)
This thesis is concerned with investigations of two largely dissimilar problems, which are treated in separate Parts. In Part I, uranium-lead studies of five pitchblende specimens from four localities in Cornwall are described. Chemical analysis for uranium in the pitchblendes was effected by chromatographic separation on a cellulose column, followed by gravimetric finish as the oxide. For lead, a dithizone separation was used, followed by gravimetric finish as the sulphate. Dithizone-separated lead was precipitated as lead sulphide for mass spectrometric analysis. The mass spectrometer used throughout this work was a Metropolitan-Vickers Type MS 5 instrument with 12 in. radius, 90° analyser tube, using volatilization of solid lead sulphide from a heated tungsten triple filament as ion source. The isotopic measurements of Moorbath of seven galenas from S. W. England were used to correct for the presence of common lead which was relatively high in all specimens. The 206/233 and 207/235 ages obtained are concordant within experimental errors for all specimens (207/206 ages arc unreliable in this age range). The 206/233 ages are considered the most significant, and these fall into three groups of values - 225 m.y., 124 m.y., 60 m.y. - which are markedly different from the only other concordant U/Pb age of 290 m.y. reported for Cornwall, and from the mean K/Ar and Rb/Sr ago of 230 m.y. determined for the Dartmoor granite. X-ray powder diffraction photos wore taken of all pitchblende specimens analysed for age determination, Calculation of cell sizes show that these decrease with decreasing age. Decreasing cell sizes are due to increasing digress of oxidation of uranium in the pitchblendes. Autoradiograph and polished section studies show that recent weathering has not affected the specimens, that radon loss is unlikely, and that uranium is present as coffinite as well as pitchblende in all specimens. A unique interpretation of the data cannot yet be made. The following main possibilities are discussed in detail:- The ages represent periods of primary mineralisation. Lead loss has made the ages apparently low. The specimens have all been mineralised at the same period, but have been remobilised at one or more later periods. The third hypothesis is considered the most likely. The observation of an abnormal radiogenic component in a galena specimen from the same deposit as a pitchblende specimen would be good evidence for remobilisation. However, galena from the South Terras lode has normal isotopic composition. No other galena from the same deposit as a pitchblende specimen studied was available for isotopic analysis. The following conclusions are consistent with the evidence available, but are necessarily tentative:- The 60 m.y. age represents a period of local remobilisation of pitchblendes - and possibly also of other hydrothermal minerals - in Cornwall in early Tertiary times. The 124 m.y. age may represent a similar period of remobilisation in early Cretaceous times. The 225 m.y. age may represent a primary mineralisation. Alternatively, only a 60 m.y. event may have occurred, which partially reduced the ages of original 225 m.y. or 280 m.y. old pitchblende to give intermediate values. Many more pitchblende specimens must be studied by all the techniques applied in this work before these problems can be conclusively solved. In Part II, the results of isotope analyses of 74 galena specimens (63 from Ireland and 11 from France) are reported. Each specimen was analysed at least twice. The agreement generally obtained between replicate results indicates that the precision of the percentage Pb204 figures quoted is within 0.4%, and of the percentage Pb206, Pb207, and Pb208 figures is within 0.2%. The iso topic analysis of two inter-laboratory lead reference samples gave close agreement with other results obtained using the solid source volatilization technique; agreement was not so close with results obtained using gas sources. Lead sulphide precipitates were chemically prepared from all galena specimens for use as samples for isotopic analysis. An alternative sample form for isotopic analysis of fine crushed galena, separated on the micropanner from contaminating minerals in the specimen, was also found to be most satisfactory. The digital computer was applied throughout this work to:- the correction for non-linearity in the recorder of the mass spectrometer. the calculation of lead isotope and model parameter results from the raw data of each mass spectrometer run. the calculation of tables for solving the Holmes-Houtermans equation accurately; copies of these tables are included inside the back cover. the calculation of lead model ages and geochemical ratios from lead isotope ratios and abundances. Copies of these programmes and specimen series of data and results are included at the end of this thesis. Moorbath's isotope data for 17 galenas from Ireland have also been included, so that all the 80 galenas, which have been isotopically analysed from Ireland so far, are discussed in this thesis. The Holmes-Houtermans model was used for the interpretation of all the lead isotope data. Lead model ages are very sensitive to small changes in the physical constants and parameters used in their calculation. The exact effect involved is shown by some sample calculations. The models of Russell and associates were found to be inapplicable for the interpretation of these lead isotope data from Ireland and France. The Irish galenas have yielded results broadly similar to those found by Moor bath for galenas from England. Scotland and Wales. Four anomalously old galenas have been definitely identified, all from near Oughterard, Co. Galway. In addition, four Irish galenas with anomalously young (negative) model ages have been measured, the first of this type recognised in the British Isles. These latter specimens come from isolated lead occurrences at Knockybrin, Co. Donegal, Tankardstown, Co. Waterford and Slieve Binian, Co. Down. The major lead mineralisation in Ireland occurred from Ordovician to Triassic times, the most frequent mineralisation occurring between the Devonian and the Permian. Individual deposits and areas are discussed in detail. The model ages of the eleven galenas from Bretagne and Normandie, France, also range from Ordovician to Triassic values, although the few data available render these limits tentative only. A critical assessment is made of the only other isotopic measurements reported for galenas from France. Moorbath's definition of 'periods' of lead mineralisation for the British Isles has been re-examined from the distributions of the combined data of Moorbath and the author (83 galenas from England, Scotland and Wales, and 30 galenas from Ireland). It is concluded that 'periods' of mineralisation should now be defined less precisely than by Moorbath. Successive groups of model ages cannot be distinguished positively unless they are at least 80 m.y. apart. The geochemical ratios U238/Pb204 and Th232/U238 are found to exhibit significant small regional variations in Ireland, the values for both these ratios being somewhat higher in the East and South-East than in the rest of the island. The values of these geochemical ratios for the French galenas are remarkably constant despite the wide variations in their geographical and geological settings and in their model ages. One of the Appendices comprises a report of a preliminary trace element investigation into the silver, thallium and gold contents of some British galenas by neutron activation analysis. Four galenas from each of the Northern, and Southern Pennines mineralised areas were analysed. The thallium content of all galenas is close to 1 p.p.m.. The four Northern Pennines galenas have a higher silver content than the four Southern Pennines galenas.